2009
DOI: 10.1007/s10562-009-9841-1
|View full text |Cite
|
Sign up to set email alerts
|

Thiophene as Internal Promoter of Selectivity for the Liquid Phase Hydrogenation of Citral Over Ru/KL Catalysts

Abstract: The effect of thiophene (Th) addition, in the concentration range 0-6 ppm, on the performance of Ru/KL catalysts is analyzed for the liquid phase hydrogenation of citral at 323 K and 4 MPa. The results show a promoter effect of thiophene on the overall hydrogenation activity of the catalysts, with a maximum at 3 ppm concentration of Th. Particularly, it is evidenced an increase in the selectivity towards the hydrogenation of the carbonyl group of citral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The use of thiophene to promote chemoselective hydrogenation of unsaturated aldehydes has been reported on Ru [109] and Au [110] catalysts. Similarly, the modification of Pd-nanoparticles with thiols can promote the selective hydrogenation of unsaturated oxygenates [111] and amines [112].…”
Section: Sulfurmentioning
confidence: 99%
“…The use of thiophene to promote chemoselective hydrogenation of unsaturated aldehydes has been reported on Ru [109] and Au [110] catalysts. Similarly, the modification of Pd-nanoparticles with thiols can promote the selective hydrogenation of unsaturated oxygenates [111] and amines [112].…”
Section: Sulfurmentioning
confidence: 99%
“…The addition of thiophene to Ru/KL catalysts gave a maximum selectivity to geraniol and nerol of 46% (at 15% citral conversion with 3 ppm thiophene); in the absence of the thiophene, the Ru catalysts typically favor CC hydrogenation. 5 Therein, it was also reported that the adsorption mode of the thiophene (relating to thiophene concentration/surface coverage) altered whether the citral adsorbed through the CC or the CO bond. Addition of ethylenediamine during the hydrogenation of citral over a Ru/AlO(OH) catalyst (in water) resulting in 87% selectivity to geraniol/nerol (93% conversion), whereas selectivity of 74.3% (at 60.5% conversion) was obtained without the additive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…69 Such experimental and theoretical studies help to explain the enhanced selective hydrogenation of a,b unsaturated aldehydes to allylic alcohols over Cu/Al 2 O 3 and Ru/KL zeolite catalysts in the presence of trace thiophene. 70,71 High selectivity in the crotonaldehyde/S-Cu( 111) system may also reflect the formation of crotyl alcohol molecules themselves possessing a significant CQC bond tilt, which, as for acrolein, may protect the unsaturated alcohol against further hydrogenation to n-butanol.…”
Section: Hydrogenationmentioning
confidence: 99%